2014
DOI: 10.1097/olq.0000000000000106
|View full text |Cite
|
Sign up to set email alerts
|

Opt-Out Screening for Chlamydia trachomatis and Neisseria gonorrhoeae in Female Detainees at Cook County Jail in Chicago, IL

Abstract: Women entering the Cook County Jail have high prevalence of GC/CT infections. Opt-out screening increased the number of GC and CT diagnoses made, and a high proportion of women were treated while incarcerated. Significant challenges remain in ensuring that screening is completed for all women who do not opt out and in providing treatment to women with short duration of incarceration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
22
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 8 publications
3
22
0
3
Order By: Relevance
“…In 7 studies, opt-in testing at entry was compared with client-initiated testing. In all cases, the opt-in testing modality resulted in higher uptake rates across diseases ( 13 , 31 , 45 , 86 88 ). Kim et al ( 46 ) reported that patients with HCV detected through active case finding were twice as likely to be asymptomatic as compared with those detected through client-initiated testing (relative risk = 2.0; P = 0.09).…”
Section: Resultsmentioning
confidence: 91%
See 4 more Smart Citations
“…In 7 studies, opt-in testing at entry was compared with client-initiated testing. In all cases, the opt-in testing modality resulted in higher uptake rates across diseases ( 13 , 31 , 45 , 86 88 ). Kim et al ( 46 ) reported that patients with HCV detected through active case finding were twice as likely to be asymptomatic as compared with those detected through client-initiated testing (relative risk = 2.0; P = 0.09).…”
Section: Resultsmentioning
confidence: 91%
“…Opt-out testing was only described in studies conducted outside the EU/EEA and exclusively as a modality for HIV active case finding ( 13 , 29 ). Client-initiated testing was described as a complementary approach to opt-in offered during imprisonment for HIV ( 47 , 53 ) or reported as comparator in a few additional studies investigating the effect of different testing modalities for HCV ( 35 , 45 ), HIV ( 13 ), and STIs ( 31 , 85 89 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations